Analisis Konten Buku Teks Fisika SMA/MA Kurikulum 2013 pada Pokok Bahasan Alat Optik - Shofia, Nurul; Putra, Ngurah Made Dharma; Wahyuni, Siti (UPEJ Unnes Physics Education Journal, 2019)
This research aims to revealing profile of science process skills, profile of questions, and structure of conceptual presentation in physics textbooks on the subject of optical tools. The research method used is descriptive analysis with a quantitative-qualitative approach. Sample of this research are two physics textbooks based on the 2013 Curiculum those widely used as learning resources in Cilacap district. The results showed that both textbooks on the subject of optical tools more present aspects of basic science process skills than integrated science process skills. The percentage aspects of basic science process skills is 72,88% for book A and 87,32% for book B. Questions are more dominant to train students at the level application (C3) with percentage 66,67% for book A and 71,37% for book B. The structure of presentation of the concept in book A prepared directly on the discussion of optical tools, whereas in book B is explained about reflection and refraction firstly, then review the material of optical tools.